Enhancing Students’ Speaking Skill by Applying Think Pair Share Technique to the Seventh Grade Students of SMP Tri Sakti Lubuk Pakam - Tania Sitorus; Novalina Sembiring; Fiber Yun Ginting (Sublim: Jurnal Pendidikan, 2023)
This research was mainly conducted in order to prove that Think Pair Share Technique could improve speaking skill of the seventh grade students of SMP Tri Sakti Lubuk Pakam and to describe their responses towards think pair share technique in the processes of learning speaking skill. The quantitative data analysis showed the mean score increase from 41,7 in Pre-test with 0% of the students got score ≥ 70, in Formative-test 49,16 with 0% of the students got score ≥ 70, and 60,52 in Post-test with 55,55% of the students got score ≥ 70. This is Classroom Action Research (CAR). The research findings showed that teaching speaking skill by applying Think Pair Share Technique to the seventh grade students of SMP Tri Sakti Lubuk Pakam could improve their speaking skill. It is advisable that English teachers try applying Think Pair Share Technique in teaching speaking skill